Training in Compensatory Strategies Enhances Rapport in Interactions Involving People with Möbius Syndrome - Michael, John; Bogart, Kathleen; Tylén, Kristian; Krueger, Joel; Bech, Morten; Østergaard, John Rosendahl; Fusaroli, Riccardo (Frontiers in Neurology, 2015)
In the exploratory study reported here, we tested the efficacy of an intervention designed to train teenagers with Möbius Syndrome (MS) to increase the use of alternative communication strategies (e.g. gestures) to compensate for their lack of facial expressiveness. Specifically, we expected the intervention to increase the level of rapport experienced in social interactions by our participants. In addition, we aimed to identify the mechanisms responsible for any such increase in rapport. In the study, five teenagers with MS interacted with three naïve participants without MS before the intervention, and with three different naïve participants without MS after the intervention. Rapport was assessed by self-report and by behavioral coders who rated videos of the interactions. Individual nonverbal behavior was assessed via behavioral coders, while verbal behavior was automatically extracted from the sound files. Alignment was assessed using cross recurrence quantification analysis and mixed effects models. The results showed that observer-coded rapport was greater after the intervention, whereas self-reported rapport did not change significantly. Observer-coded gesture and expressivity increased in participants with and without MS, while overall linguistic alignment decreased. Fidgeting and repetitiveness of verbal behavior also decreased in both groups. In sum, the intervention may impact nonverbal and verbal behavior in participants with and without MS, increasing rapport as well as overall gesturing, while decreasing alignment.